Multi-stakeholder analysis to improve agricultural water management policy and practice in Malta - D’Agostino, Daniela; Borg, M.; Hallett, Stephen H.; Sakrabani, Ruben; Thompson, Andrew J.; Papadimitriou, Lamprini; Knox, Jerry W. (Elsevier, 2019)
Malta faces a raft of water challenges which are negatively impacting on the sustainability of irrigated agriculture, and creating serious tensions with other sectors competing for water, including urban development, tourism and the environment. In this paper we argue for a transparent process centred on participatory stakeholder engagement to agree on the most challenging water-related risks and to identify solutions that both support the water governance framework and improve on-farm water management practices. Given Malta’s dependence on freshwater, this study focused on outdoor field-scale irrigated production. A three staged stakeholder-driven approach was developed. The first stage included Delphi analyses to identify the key constraints on water management and fuzzy cognitive mapping to enable stakeholders to analyse their mental models and formalise conceptual and causal relationships between different components impacting on Maltese agriculture. Secondly, questionnaires were used to inform understanding of national policy gaps in water management and thirdly, a “backcasting” stakeholder workshop was used to identify policy actions to achieve a more sustainable future for agriculture on the island. The study confirmed that Malta’s core challenge is tied to poor water governance and the need to define policies that are socially and environmentally acceptable and geared to tackling the complex water challenges the agricultural sector faces. Developing support for farmer training, knowledge translation, greater public awareness of the importance and value of water for high-value crop production and multi-sector collaboration to promote shared opportunities for water infrastructure investment were highlighted as potential solutions. The findings have direct relevance to other island communities where water scarcity poses serious agronomic risks to production and where agriculture underpins rural livelihoods and the economy.
Keywords: Climate change; Groundwater; Irrigation; Risk; Water resources